Canada in the frame : copyright, collections and the image of Canada, 1895-1924 - Hatfield, Philip J. (Modern Americas., 2018)
Canada in the Frame explores a photographic collection held at the British Library that offers a unique view of late nineteenth-century and early twentieth-century Canada. The collection, which contains in excess of 4,500 images, taken between 1895 and 1923, covers a dynamic period in Canada's national history and provides a variety of views of its landscapes, developing urban areas and peoples. Colonial Copyright Law was the driver by which these photographs were acquired; unmediated by curators, but rather by the eye of the photographer who created the image, they showcase a grass-roots view of Canada during its early history as a Confederation.